FEASIBILITY STUDY ON ESTABLISHING THE INTERNATIONAL CENTRE FOR SOCIAL WELFARE AND SOCIAL POLICY - Ćukalović, Vukica (Ревија за социјална политика/Journal of Social Policy, 2015)
The feasibility study is a planned activity, caused and shaped by social motives reflecting through the specific features of the constant process (from one system of values into another system of values). The accompanying experience imposes a need of efficient implementation and proper practice of social work in resolving of all transitional effects. This implies knowledge in action or the ability to use knowledge, personal capacity and resources. The objective is defined by initiating the process of changes as the ability of a social worker for permanent upgrading of the professional role, authenticity, dignity and based on the values and skills of the social work.